Reading chest radiographs for pneumoconiosis by computer. - Jagoe, J R (1975)
Computer programs for measuring simple pneumoconiosis in radiographs are described and assessed. The 36 films studied had been read by 11 skilled human observers and a 'radiological score' of pneumoconiotic severity was therefore available for each film. The computer assigns to each square grid of side 3-6 mm a measure which reflects the unevenness of the density distribution in that grid. The 'computed score' is defined as the mean diversity over all relevant grids in both lung fields. On the set of 36 films the correlation between radiological score and computed score was 0-88. By contrast, the correlation between the score assigned by a single observer and the average of the scores assigned by the other 10 was in the range 0-95 to 0-98. The program can use the computed score to classify a film into one of the four major International Labour Office (ILO) U/C categories, the success rate of this process being 80% compared with those quoted by other workers in the range 45%-65%. If the films used in this study be typical, then the program described may form the basis of an automatic method for measuring pneumoconiosis in epidemiological work.